American wildflowers : a literary field guide - Barba, Susan; Shapton, Leanne (Abrams, 2022)
American Wildflowers: A Literary Field Guide collects poems, essays, and letters from the 1700s to the present that focus on wildflowers and their place in our culture and in the natural world. Editor Susan Barba has curated a selection of plants and texts that celebrate diversity: There are foreign-born writers writing about American plants and American writers on non-native plants. There are rural writers with deep regional knowledge and urban writers who are intimately acquainted with the nature in their neighborhoods. There are female writers, Black writers, gay writers, indigenous writers. Included here is the work of botanists such as William Bartram, George Washington Carver, and Robin Wall Kimmerer, and horticultural writers like Neltje Blanchan and Eleanor Perényi. There are prose pieces by Aldo Leopold, Lydia Davis, and Aimee Nezhukumatathil. And most of all, there are poems: from Walt Whitman and Emily Dickinson, William Carlos Williams and T. S. Eliot to Allen Ginsberg and Robert Creeley, Lucille Clifton and Louise Glück, Natalie Diaz and Jericho Brown. The book includes exquisite watercolors by Leanne Shapton throughout and is organized by species and botanical family--think of it as a field guide to the literary imagination.